A pedagogical movement and the pedagogic in movement: Freirean strands of communication and community broadcasting (Práxis Educativa, 2020)
The focus of this study is about alternative popular communication movements, specifically those called Community Broadcasting. Taking the bibliographic research as a methodological strategy, the objective was to analyze the contributions of Paulo Freire’s educational thinking to the formulation of a potentially more horizontal and participatory communication proposal in Brazil and Latin America. Based on the work of Paulo Freire and authors in the field of communication, the following are the main Freirean contributions: the idea that communicating, informing and educating are inseparable elements in social communication; the complaint about banking practices in education and communication; facing the monopoly of the word and encouraging everyone to make their voice heard; the premise that the intelligibility of the world is constituted in the human-world interaction ; and, finally, the dialogical character of human communication as the driving force of a more democratic media proposal.Keywords: Community Broadcasting. Communication. Paulo Freire.